Protection of Freedom of Expression Through Social Media from The Perspective of Human Rights - Amatus Venantius Sabubun; Roberth Kurniawan Ruslak Hammar (Green Publisher Indonesia, 2024)
Freedom of expression is one of the fundamental human rights guaranteed in various international legal instruments. The development of information and communication technology, especially social media, has opened up new spaces for people to express their opinions. This research aims to analyze the protection of the right to freedom of opinion through social media from a human rights perspective. This research uses normative legal research methods with a qualitative approach. Research data was obtained through literature studies of various statutory regulations, books, scientific journals and other legal sources. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the protection of freedom of expression on social media is regulated in various policies including the Universal Declaration of Human Rights (UDHR), the International Convention on Civil and Political Rights (ICCPR), and the European Convention for the Protection of Human Rights and Fundamental Freedoms (ECHR). Meanwhile, in Indonesia it is regulated in the 1945 Law, the Human Rights Law, and Law Number 19 of 2016. The right to freedom of opinion through social media is a fundamental human right that needs to be protected. This right is considered a fundamental right that cannot be reduced or limited by anyone or the state, this emphasizes the need for strong fulfillment and protection of this right. However, this right also needs to be balanced with the responsibility to use it wisely and responsibly.